Skills For Composition and Decomposition of Flat Shape of Class III Students Using Geostick Media in the Pmri Approach - Syahrani, Naela; Sari, Nisa Aulia; Zuliana, Eka (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to capture students' skills in composing and decomposing plane figures using geostick media within the framework of the Indonesian Realistic Mathematics Education (PMRI) approach. Geosticks were chosen as a teaching aid due to their ability to concretely visualize geometric shapes, making it easier for students to understand abstract concepts. This research employs a descriptive qualitative method involving direct observation of students' skills in assembling and disassembling plane figures. The findings reveal that geostick media can enhance third-grade students' skills in composing and decomposing plane figures. However, some students encountered difficulties in forming more complex shapes, which required additional guidance from the teacher. Overall, this study indicates that contextual learning media, such as geosticks within the PMRI approach, can improve third-grade students' skills in composing and decomposing plane figures.